Efficiency Advantages of the Separated Electric Compound Propulsion System for CNG Hybrid Vehicles - Emiliano Pipitone; Salvatore Caltabellotta (Energies, 2021)
As is widely known, internal combustion engines are not able to complete the expansion process of the gas inside the cylinder, causing theoretical energy losses in the order of 20%. Several systems and methods have been proposed and implemented to recover the unexpanded gas energy, such as turbocharging, which partially exploits this energy to compress the fresh intake charge, or turbo-mechanical and turbo-electrical compounding, where the amount of unexpanded gas energy not used by the compressor is dedicated to propulsion or is transformed into electric energy. In all of these cases, however, maximum efficiency improvements between 4% and 9% have been achieved. In this work, the authors deal with an alternative propulsion system composed of a CNG-fueled spark ignition engine equipped with a turbine-generator specifically dedicated to unexpanded exhaust gas energy recovery and with a separated electrically driven turbocompressor. The system was conceived specifically for hybrid propulsion architectures, with the electric energy produced by the turbine generator being easily storable in the on-board energy storage system and re-usable for vehicle traction. The proposed separated electric turbo-compound system has not been studied in the scientific literature, nor have its benefits ever been analyzed. In this paper, the performances of the analyzed turbo-compound system are evaluated and compared with a traditional reference turbocharged engine from a hybrid application perspective. It is demonstrated that separated electric compounding has great potential, with promising overall efficiency advantages: fuel consumption reductions of up to 15% are estimated for the same power output level.